Bilateral ruptured tubal pregnancy: a case report - Kour, Gagandeep; Dhar, Tapasya; Jaiswal, Shristi; Sobti, Vijeta; Isaacs, Roma (International Journal of Research in Medical Sciences, 2017)
The infrequency with which Bilateral Tubal Pregnancy (BTP) occurs makes it a rare entity with an estimated incidence of 1 in 2,00,000 of all pregnancies and about 0.1 percent of all ectopic pregnancies. In the last few decades enhancement in the rate of occurrence has been reported in literature which has been attributed to Assisted Reproductive Technology (ART), Intra-Uterine Devices (IUD) and Pelvic Inflammatory Diseases (PID). We report a case of ruptured BTP where rupture of one tube preceded the rupture of contralateral side by approximately 3 weeks. 30 years old G4P2L1A1 presented with complaints of nausea and vomiting, vaginal bleeding and pain lower abdomen. There was no history of ART, IUCD or PID. A presumptive diagnosis of ruptured tubal pregnancy was made on the basis of clinical examination and ultrasound findings and patient was taken up for laparotomy. There was a right tubo-ovarian mass with bleeding from ruptured tube. Right salpingo-oophrectomy was done. Left tube on examination revealed a mass with a bleeding rent. Left salpingectomy was done because of extensive damage. Bilateral ruptured tubal ectopic pregnancy was confirmed on histopathological examination. BTP is likely to be missed even during USG as was in this case. This emphasizes the need to thoroughly examine pelvis for any other ectopic gestation during laparotomy.